WATER QUALITY AND TROPHIC STATE INDEX OF THE PEQUIA WATERSHED - MA - Rizzo, Felipe Alexandre; Nery, Liliane Moreira [UNESP]; Tonello, Paulo Sergio [UNESP]; Cunha e Silva, Darllan Collins da [UNESP] (Univ Federal Goias, Dept Geografia, 2022)
Monitoring water quality becomes a useful and relevant tool for planning and taking actions that guarantee water conservation. Water quality indicators are commonly used because they are easy to interpret, supporting decision-making. Therefore, the present study aims to analyze the physical-chemical and biological parameters from the Water Quality Index (WQI) and the Trophic State Index (TSI) of the Pequia Stream and its tributaries, as well as to obtain such indexes. For this, five points were sampled, and nine parameters were analyzed. Regarding the WQI, the results varied between Medium and Bad, and as for the TSI the results varied between Mesotrophic and Eutrophic. We concluded that the results obtained were influenced by the seasonal period analyzed, the presence of macrophytes, and a load of nutrients from sewage disposal that contributed to the eutrophication process. Therefore, it is suggested that the monitoring of surface waters in the area studied be continued.
Keywords: Eutrophication; Anthropization; Water quality; Spatial analysis